Risk factors associated with the failure of day surgery for total knee arthroplasty a multivariate logistic regression analysis - Luo, Pan; Feng, Jiabin; Li, Yankun; Zou, Yingli; Zhu, Xuepeng; Sun, Li; Li, Bo (Frontiers in Surgery, 2025)
ObjectiveTo explore and analyze the risk factors leading to delayed discharge in patients undergoing day surgery for total knee arthroplasty, providing a theoretical basis for optimizing patient selection, targeted interventions, and managing expectations and risks of day surgery patients.MethodsA retrospective analysis of clinical data from patients diagnosed with “knee osteoarthritis” and scheduled for day surgery for total knee arthroplasty at the Department of Orthopedics, Guizhou Provincial People's Hospital from October 2021 to June 2023. Patients were divided into a normal discharge group and a delayed discharge group based on whether their hospital stay exceeded 48 h. Univariate analysis and multivariate logistic regression analysis were used to identify potential risk factors between the two groups.ResultsAmong the 233 patients scheduled for day surgery for total knee arthroplasty, 82 experienced delayed discharge. Univariate analysis showed that age (P = 0.042), glomerular filtration rate (P = 0.011), diabetes history (P = 0.046), disease duration (P = 0.012), knee flexion range of motion (P < 0.001), knee flexion contracture degree (P = 0.006), and surgery time (P = 0.002) had statistically significant differences between the two groups. Multivariate logistic regression analysis revealed that disease duration (P = 0.017), knee flexion range of motion (P < 0.001), glomerular filtration rate (P = 0.010), and surgery time (P = 0.020) were independent risk factors. Additionally, postoperative motor function decline or sensory impairment, pain, dizziness or orthostatic hypotension, postoperative limb swelling, postoperative nausea and vomiting, bleeding and exudation, and psychosocial factors were the main reasons for delayed discharge.ConclusionsOur study found that disease duration, knee flexion range of motion, glomerular filtration rate, and surgery time are independent risk factors for delayed discharge after day surgery for total knee arthroplasty. Patients with a disease duration of more than 8 years, preoperative flexion range of motion less than 90°, and low estimated glomerular filtration rate may not be suitable for day surgery for total knee arthroplasty. Surgeons should make adequate preoperative preparations and plans, refine surgical skills, and shorten surgery time under the premise of ensuring surgical effects to reduce the risk of postoperative delayed discharge.